PENGARUH PELATIHAN DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT JASA RAHARJA CABANG MALUKU - Muhammad Amin Tamamala; Abdul Haris Tamalene; VICTOR NAHUWAY (Jurnal Administrasi Terapan, 2024)
The Effect of Training and Work Discipline on Employee Performance at PT Jasa Raharja Maluku Branch,This research is inseparable from the Human Resources of a company. For this reason, the author made this study to find out and analyze the influence of training and work discipline on employee performance at PT Jasa Raharja Maluku Branch. Data analysis was carried out quantitatively, the population in this study was 30 employees of PT Jasa Raharja Maluku Branch and the sample used in this study was 30 people. The data collection technique in this study uses questionnaires and documentation used to obtain data on PT Jasa Raharja Maluku Branch, and the data analysis technique in this study uses Validity Test, Normality Test, Reliability Test, multiple linear regression test, t test and f test and determination coefficient. The data processing in this study uses the SPSS program (version 26).The results of this study show that Training (X1) has a positive and significant effect on Employee Performance (Y) at PT Jasa Raharja Maluku Branch, Work discipline (X2) has a positive and significant effect on employee performance (Y) at PT Jasa Raharja Maluku Branch, Training and Work Discipline have a positive and significant effect on Employee Performance at PT Jasa Raharja Maluku Branch. Keywords: Training, Work Discipline, Employee Performance